Pernikahan Adat Suku Sasak dalam Perspektif Hukum Islam - Ainiyah, Qurrotul; Aryani, Mira (Proceedings of Annual Conference for Muslim Scholars, 2023)
Marriage law in Islam regulates human life in giving vent to their sexual desires in the right way so that their descendants can be maintained and becomes dignified creatures. Some community have own procedures for the marriage process. The research which was carried out in Teruwai, Pujut, Central Lombok, NTB, was aimed to describe the marriage process of Sasak Islamic community from an Islamic law perspective. This research used qualitative method. Data was collected through interviews, observation and documentation. The results were found: the way of Sasak Islamic community in Teruwai marriage is begun with Midang and Memariq which in Islam is known as Ta'aruf and Khitbah. Followed by Mangan Merangkat, Selabaran, Bait Wali, and Betikah/Bekawin, namely implementation of the marriage contract, and closing with the Roah Tradition, Sorong Serah aji Krame, Nyongkolan, Bales Ones Nae or walimatul 'Ursy in Islam.